Think-Aloud Protocol as a Method for Exploring and Understanding the Argumentation Skills of Pre-Service Science Teachers - Hendratmoko, Ahmad Fauzi; Puspitarini, Sapti; Budiyanto, Mohammad; Rahman, Nanang; Septaria, Kiki; Marpuah, Siti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Argumentation is a core component of critical thinking, one of the essential 21st-century skills. However, exploring this skill remains a challenge, often due to limitations in the available assessment methods. This study aims to offer a solution by utilizing the think-aloud protocol to explore and better understand the argumentation skills of Pre-Service Science Teachers (PSTs). A total of 30 PSTs from a state university in Indonesia participated in the research. Data collection and analysis through the think-aloud protocol were conducted in several stages: procedural briefing, implementation, coding and video analysis, and data interpretation. The findings revealed that the think-aloud protocol was effective in providing deeper insights into argumentation skills and yielded more detailed and accurate data across five key components: claims, evidence, reasoning, counterarguments, and rebuttals. On average, the PSTs demonstrated beginner-level argumentation skills, with the strongest performance in the claim component and weaker results in supporting aspects. Specifically, 5 participants were categorized as proficient, 9 as advanced, 6 as intermediate, and 10 as beginners. These results highlight the need for more effective learning strategies that provide PSTs with greater opportunities to practice constructing and critiquing arguments.